A Result on an Integral Involving Product of Two Generalized Hypergeometric Functions and Its Applications - Basnet, Ganesh Bahadur; Pahari, Narayan Prasad; Poudel, Madhav Prasad (Journal of Nepal Mathematical Society, 2024)
The aim of this research note is to provide an interesting integral involving product of generalized hypergeometric functions. This is achieved with the help of a known integral involving hypergeometric function available in the literature. Several results obtained earlier by Harsh et al. [5] follow special cases and some applicable particular examples of our main findings.